2014
DOI: 10.1051/shsconf/20141201058
|View full text |Cite
|
Sign up to set email alerts
|

Rail travel: Conceptualizing a study on slow tourism approaches in sustaining rural development

Abstract: Abstract. Rail transportation in Peninsular Malaysia is a popular transportation mode for locals to return to their hometown but is not frequently used as the mode of transport when travelling for holidays. Rural towns in Peninsular Malaysia have immense opportunity to be promoted as a popular tourism destination without the need of intense modern development. Using train rather than taking a car or a bus would endorse the concept of slowness during travel enabling tourists to enjoy the time taken to travel ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These are premises of slow tourism, a complex concept (Manthiou et al, 2022) that encourages sustainable mobility and local placetelling (Pollice, 2022). Even before the outbreak of the pandemic, slow tourism established itself as the new trend in contemporary tourism (Moira et al, 2017), especially in Italy, represented by tourists who privilege sustainable and slow mobility (Le Busque et al, 2021), such as bikes and walking, but also trains for longer distances (Dickinson & Lumsdon, 2010;Maggi, 2022;Noor et al, 2014). Furthermore, slow practice seems to be associated with a need for individual involvement (i.e., pull factors), as well as discovery and novelty, social interaction and | 6…”
Section: Slow Tourism and Inner Areasmentioning
confidence: 99%
“…These are premises of slow tourism, a complex concept (Manthiou et al, 2022) that encourages sustainable mobility and local placetelling (Pollice, 2022). Even before the outbreak of the pandemic, slow tourism established itself as the new trend in contemporary tourism (Moira et al, 2017), especially in Italy, represented by tourists who privilege sustainable and slow mobility (Le Busque et al, 2021), such as bikes and walking, but also trains for longer distances (Dickinson & Lumsdon, 2010;Maggi, 2022;Noor et al, 2014). Furthermore, slow practice seems to be associated with a need for individual involvement (i.e., pull factors), as well as discovery and novelty, social interaction and | 6…”
Section: Slow Tourism and Inner Areasmentioning
confidence: 99%
“…Slow tourism is an alternative form of tourism that originated from the philosophy of slowness, which stands in contrast to our modern fast, busy, and competitive lifestyle. Since the phenomenon of slow tourism is relatively new and has only started to gain attention in the academic literature during the last decade [2][3][4][5][6][7][8][9], there is no consensus among researchers about its exact definition or its key principles. However, the importance and potential of slow tourism as an emergent market segment have been proven by empirical data [10].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the present interest in alternative forms of tourism as opposed to mass tourism and the global shift toward sustainable tourism, one strategy could be promoting travel by the Trans-Siberian Railway as a slow tourism experience. Previous studies have shown that the concept of "slowing down" can be adapted and applied as a destination marketing strategy to locations all around the world by using different dimensions of slow tourism based on place characteristics [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%